Perceiving of Defect Tolerance in Perovskite Absorber Layer for Efficient Perovskite Solar Cell - Mahjabin S.; Haque M.M.; Sobayel K.; Jamal M.S.; Islam M.A.; Selvanathan V.; Assaifan A.K.; Alharbi H.F.; Sopian K.; Amin N.; Akhtaruzzaman M. (Institute of Electrical and Electronics Engineers Inc., 2023)
Computer software; Defect density; Optical properties; Perovskite; Absorber thickness; Deep-level defects; Defect tolerance; Fabrication process; Perovskite layers; Power conversion efficiencies; Solar cell parameters; Structural and optical properties; Perovskite solar cells